East Java Smes : Transformation Towards Independence and Sustainability - Aristyanto, Erwan; Waras, Waras; Bayu Murti, Agung (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This research aims to formulate a model for strategies to enhance the competitiveness and sustainability of SMEs while supporting economic independence in East Java. The study employs a descriptive qualitative approach with data collected through observation, interviews, and documentation, and analyzed using data reduction, data display, data triangulation, and data verification. Key informants include SME actors, relevant agency officials, representatives from East Java’s SME banks, and academics. The findings indicate that competitiveness strategies focus on digital marketing (social media, marketplaces, e-commerce), product and process innovation (unique and quality products, production efficiency), and partnerships with government, financial institutions, and large companies to expand market access and resources. Sustainability strategies emphasize prudent financial management (cash flow, affordable financing), compliance with legal and certification requirements (PIRT, halal, BPOM), and potential adoption of circular economy concepts. Strategies supporting SME independence include entrepreneurship training, mentoring, access to capital, and facilitation of business matching and exhibitions. The government and supporting institutions play a key role in creating a conducive ecosystem. Competitiveness, sustainability, and independence are synergistic: enhanced competitiveness contributes to economic sustainability, sustainability enables continuous innovation, and independence empowers SMEs to make strategic decisions and adapt effectively. Overall, SMEs in East Java have strong potential for growth and economic contribution. Sustained support through appropriate policies, empowerment programs, and resource facilitation is essential to achieve SMEs that are competitive, sustainable, and fully independent.